Selecting the Appropriate Geometrical Parameters of made in Viet Nam Carbide Insert for Best Roughness and Dimensional Accuracy during Contour Turning of SUS304 Stainless Steel - Tuyen, Bui Ngoc; Cong, Nguyen Chi (Old Journal, 2017)
This paper presents an experimental study for selecting the appropriate geometrical parameters such as nose radius r, rake angle γ, relief angle α, elevation angle λ … of carbide insert, which is made in Viet nam, to ensure best surface roughness and dimensional accuracy contour turning SUS304 stainless steel with convex curved profile on the CNC lathe. Method of experimental design and analysis of variance such as Taguchi and ANOVA were used to assess the influence level of the geometric parameters of cutting tools on the two targets. The study results shows that the best surface roughness and the dimensional accuracy, assessed by the deviation of the machining diameter AD, the rake angle γ(-5°) have the the greatest influence level, Followed by the contribution percentages for the nose radius r, the relief angle α, the elevation angle λ. By analysis and synthesis on the experimental results, the study also finds out the optimized parameters to achieve the best surface roughness and dimensional accuracy simultaneously as follows: the rake angle γ (-5°), the nose radius r (0.4 mm),the elevation angle λ (-6°), the cutting edge angle φ (93°), and side angle α (35°).